Evaluation of a polyherbal topical aerosol spray as a supportive therapy for clinical mastitis in dairy cows - Selvam, Ramasamy; Sureshbabu, Ganapa; Saravanakumar, Marimuthu; Prashanth, DSouza (Journal of Advanced Veterinary and Animal Research, 2015)
The present study was designed to evaluate the polyherbal topical aerosol spray Wisprec® Advanced (M/S. Natural Remedies Private Limited, India) as a supportive therapy for clinical mastitis in dairy cows. A total of 41 dairy cows suffering from clinical mastitis were selected, and Wisprec® Advanced was sprayed on mastitis affected quarters of udder two times a day along with a parenteral antibiotic till complete recovery. The rectal temperature, pain on palpation of udder, swelling of udder, consistency of milk, recovery period and product satisfaction score were assessed to evaluate the efficacy of Wisprec® Spray. Topical application of Wisprec® Advanced Spray have shown a significant improvement (P<0.001) in alleviation of rectal temperature, pain on palpation of udder and swelling of udder, and the consistency of milk was restored to normal after 3 to 4 days of treatment. The results demonstrate that the Wisprec® Advanced spray could be considered as an alternative to non-steroidal anti-inflammatory drugs (NSAIDs) as a supportive therapy for clinical mastitis of dairy cows. http://dx.doi.org/10.5455/javar.2015.b87